SETTLEMENT OF APARTMENT ARREARS ON A NON-LITIGATION BASIS BETWEEN MRS. MP AND PT. ELITE ON CONSUMER PROTECTION LAWS - Gunawan, Indra (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2021)
Consumer protection is a consequence of the force of law in meeting the interests of consumers. This requires a balance between the quality of service so that creditors/banks improve the quality of service in a fair (honest) manner to inform in detail about advertising and other services. to the ever-changing demands of this era of globalization. The legal force in information is a means of consumer protection in an agreement that is mutually binding between rights and obligations. Consumer protection law as the basis for the settlement of peace underhand on the heading